Playable Case Studies: A New Educational Genre for Technical Writing Instruction. Issue 4 (2nd October 2019) - Balzotti, Jon; Hansen, Derek
ABSTRACT: A Playable Case Study (PCS) is a hybrid learning experience where students (1) participate in a fictional narrative that unfolds through an immersive, simulated environment and (2) engage in classroom activities and lessons that provide educational scaffolding and promote metacognition through in-game and out-of-game experiences. We present the Microcore PCS to illustrate the potential of this new type of experiential simulation that incorporates aspects of Alternate Reality Games (ARGs) to increase immersion and teach workplace literacies in the technical communication classroom. We explore results from a pilot test of Microcore with an undergraduate technical communication course, identifying design strategies that worked well and others that led to improvements that are currently being incorporated. We also provide questions to prompt future research of playable case studies and discuss our findings in a broader context of technical communication pedagogy.